Novel therapeutic targets for primary open-angle glaucoma identified through multicenter proteome-wide mendelian randomization - Yuan, Weichen; Li, Jun; Gao, Shang; Sun, Wei; Zhao, Fangkun (Frontiers in Pharmacology, 2024)
Background: This study aimed to identify novel therapeutic targets for primary openangle glaucoma (POAG).The summary-data-based Mendelian randomization (SMR) method was used to evaluate the genetic association between plasma proteins and POAG. Two sets of plasma protein quantitative trait loci (pQTLs) data considered exposures were obtained from the Icelandic Decoding Genetics Study and UK Biobank Pharma Proteomics Project. The summary-level genome-wide association studies data for POAG were extracted from the latest Round 10 release of the FinnGen consortium (8,530 cases and 391,275 controls) and the UK Biobank (4,737 cases and 458,196 controls). Colocalization analysis was used to screen out pQTLs that share the same variant with POAG as drug targets identified. The two-sample Mendelian randomization, reverse causality testing and phenotype scanning were performed to further validate the main findings. Protein-protein interaction, pathway enrichment analysis and druggability assessment were conducted to determine whether the identified plasma proteins have potential as drug targets.Results: After systematic analysis, this study identified 8 circulating proteins as potential therapeutic targets for POAG. Three causal proteins with strong evidence of colocalization, ROBO1 (OR=1.38, p=1.48×10 -4 , PPH4=0.865), FOXO3 (OR=0.35, p=4.34×10 -3 , PPH4=0.796), ITIH3 (OR=0.89, p=2.76×10 -4 , PPH4=0.767), were considered tier 1 targets. Five proteins with medium support evidence of colocalization, NCR1 (OR=1.25, p=4.18×10 -4 , PPH4=0.682), NID1 (OR=1.38, p=1.54×10 -3 , PPH4=0.664), TIMP3 (OR=0.91, p=4.01×10 -5 , PPH4=0.659), SERPINF1 (OR=0.81, p=2.77×10 -4 , PPH4=0.59), OXT (OR=1.17, p=9.51×10 -4 , PPH4=0.526), were classified as tier 2 targets. Additional sensitivity analyses further validated the robustness and directionality of these findings. According to druggability assessment, Pimagedine, Resveratrol, Syringaresinol and Clozapine may potentially be important in the development of new anti-glaucoma agents.Our integrated study identified 8 potential associated proteins for POAG.These proteins play important roles in neuroprotection, extracellular matrix regulation and oxidative stress. Therefore, they have promising potential as therapeutic targets to combat POAG.